About Fixed Points in CAT(0) Spaces under a Combined Structure of Two Self-Mappings - Manuel De la Sen (Journal of Mathematics)
This paper investigates some fixed point-related questions including the sequence boundedness and convergence properties of mappings QtSx,Ty=tSx⊕1-tTy defined in CAT0 spaces, which are parameterized by a scalar t∈0,1, where S,T:  X→X are nonexpansive Lipschitz-continuous mappings and X,d is a metric space which is a CAT0 space.